Doctors Perception about Staying in or leaving Rural Health Facilities IN DISTRICT ABBOTTABAD - Farooq, Umer; Ghaffar, Abdul; Narru, Iftikhar Ahmed; Khan, Dilawar; Irshad, Romana (Journal of Ayub Medical College Abbottabad, 2004)
Background: An imbalance exists between offered medical services and needed health care for the people in rural areas of Pakistan. Many studies have found non-availability, of health care providers as major contributors to the poor health indicators of the rural areas. Methods and Results: An endeavor to attend the issue has been made through a cross-sectional survey of the Medical Officers working in the different health facilities of District Abbottabad. The study found that the doctors are neither trained to work in rural setups nor they are given proper facilities and service structure to work there. They perceive to face disadvantages affecting their social, professional and family life, if they join in rural areas. Recommendations: This study recommends strengthening of Community Oriented Medical Education for motivating doctors towards participation in rural health services. Doctors working in rural health facilities might be given financial and professional incentives and a conducive environment to retain them. Keywords: Health care providers, Health indicators, Rural